2019
DOI: 10.3201/eid2509.190445
|View full text |Cite
|
Sign up to set email alerts
|

Case of Plasmodium knowlesi Malaria in Poland Linked to Travel in Southeast Asia

Abstract: We report a case of Plasmodium knowlesi malaria imported to central Europe from Southeast Asia. Laboratory suspicion of P. knowlesi infection was based on the presence of atypical developmental forms of the parasite in Giemsa-stained microscopic smears. We confirmed and documented the clinical diagnosis by molecular biology techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…To date, reports of naturally acquired P. knowlesi are limited to Asia. Isolated cases of human P. knowlesi infections have been reported in Europe, North America, Japan, Australia and New Zealand but all reported individuals had histories of travel to Southeast Asia (Kantele et al, 2008, Bronner et al, 2009, Ta et al, 2010, Berry et al, 2011, Hoosen and Shaw, 2011, Bart et al, 2013, Tanizaki et al, 2013, Cordina et al, 2014, Seilmaier et al, 2014, Mackroth et al, 2016, Ozbilgin et al, 2016, De Canale et al, 2017, Takaya et al, 2018, Nowak et al, 2019, Roe et al, 2020. There have been no published P. knowlesi reports in travellers or other individuals in Africa or South America, potentially due to diagnosis as other malaria species in endemic regions.…”
Section: Reporting Bias and Surveillance For P Knowlesimentioning
confidence: 99%
“…To date, reports of naturally acquired P. knowlesi are limited to Asia. Isolated cases of human P. knowlesi infections have been reported in Europe, North America, Japan, Australia and New Zealand but all reported individuals had histories of travel to Southeast Asia (Kantele et al, 2008, Bronner et al, 2009, Ta et al, 2010, Berry et al, 2011, Hoosen and Shaw, 2011, Bart et al, 2013, Tanizaki et al, 2013, Cordina et al, 2014, Seilmaier et al, 2014, Mackroth et al, 2016, Ozbilgin et al, 2016, De Canale et al, 2017, Takaya et al, 2018, Nowak et al, 2019, Roe et al, 2020. There have been no published P. knowlesi reports in travellers or other individuals in Africa or South America, potentially due to diagnosis as other malaria species in endemic regions.…”
Section: Reporting Bias and Surveillance For P Knowlesimentioning
confidence: 99%
“…At the late trophozoite stage, P. knowlesi may appear as band forms, which resemble those of P. malariae. Hence, misidentification of knowlesi malaria as infections by P. falciparum or P. malariae is common, especially in areas where the microscopists are not familiar with the parasites [ 32 , 37 , 38 , 90 , 91 ]. Besides, parasites with atypical amoeboid morphology were also found in patient’s blood smears [ 92 ].…”
Section: Introductionmentioning
confidence: 99%
“…The thrombocytopenia in the present study might be related to a high parasitaemia level, as presented by a study in Thailand [ 45 ]. A previous study reported that patients with P. knowlesi malaria demonstrated a decrease in coagulation system markers [ 46 ] or an increase in the proportion of platelet binding to infected red cells [ 47 ]. The risk factors for death from P. knowlesi infection demonstrated in Sabah, Malaysia, were female sex, age ≥ 45 years, cardiovascular disease, microscopic misdiagnosis, and delay in administrating intravenous treatment [ 48 ].…”
Section: Discussionmentioning
confidence: 99%